ISLAMISTER OG KLUBLIV I GAZASTRIBEN - Jensen, Michael Irving (Tidsskriftet Antropologi, 1998)
Michael Irving Jensen: Islamists and Club Milieu in the Gaza Strip The article deals with Islamic social institutions in the Gaza Strip. The author considers these institutions as being part of Palestinian civil society. However, the bulk of the article is focused on one aspect of the work that the Islamic social institutions carry out; namely sport activities. The article is based on qualitative interviews, carried out by the author, with young men playing football in an Islamic club (ciosely related to the Hamas movement). Among the questions raised are: Why do young men choose to play football in an Islamic club? What are their perceptions of the political situation in the Gaza Strip? How do they view the relationship between Islam and politics in general? The interviews reveal - not unsurprisingly - that the young Islamists playing football do not equal the stereotype of an Islamist, i.e. a young fanatic with long beard and a wild look in the face. On the contrary, they are young men willing and able to cope with the modem world. From the interviews it is evident that high moral standards, more than anything else, attract these young men. Although further empirical work needs to be done, one could conclude tentatively that a good Islamist can play club football three times a week.